2013
DOI: 10.1159/000351186
|View full text |Cite
|
Sign up to set email alerts
|

Discharge after Primary Angioplasty at 24 h: Feasible and Safe or a Step Too Far?

Abstract: Current clinical practice regarding surveillance period and length of hospital stay after an ST elevation myocardial infarction is very variable among different countries and hospitals. In general, there has been a significant reduction in length of stay overall, which is mainly due to the increasing use of primary percutaneous coronary intervention. Length of stay after a ST elevation myocardial infaction, which is a rather common event, has a major impact on health care costs and patients' quality of life. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(24 reference statements)
0
4
0
1
Order By: Relevance
“…Current practice is widely variable across countries and centres, but it is unclear whether early hospital discharges are safe. 32 It is very reassuring that, despite the continuous reduction in hospital stay, outcomes have significantly improved (figure 1). Two new studies have demonstrated that discharging low risk STEMI patients within 2 days following primary PCI is safe and feasible.…”
Section: Optimal Duration Of Monitoring/ Hospital Staymentioning
confidence: 99%
“…Current practice is widely variable across countries and centres, but it is unclear whether early hospital discharges are safe. 32 It is very reassuring that, despite the continuous reduction in hospital stay, outcomes have significantly improved (figure 1). Two new studies have demonstrated that discharging low risk STEMI patients within 2 days following primary PCI is safe and feasible.…”
Section: Optimal Duration Of Monitoring/ Hospital Staymentioning
confidence: 99%
“…Current practice is widely variable across countries and centres, but it is unclear whether early hospital discharges are safe 32. It is very reassuring that, despite the continuous reduction in hospital stay, outcomes have significantly improved (figure 1).…”
Section: Primary Percutaneous Coronary Interventionmentioning
confidence: 99%
“…Trenutna praksa je vrlo razliËita meu zemljama i centrima te ostaje nejasno da li je rani otpust iz bolnice siguran. 32 OhrabrujuÊe je da su unatoË kontinuiranom smanjenju duljine boravka u bolnici ishodi lijeËenja znatno poboljπani (Slika 1).…”
Section: Optimalno Trajanje Bolniëkog Lijeëenjaunclassified